Religious Tradition and Technology: Debate among Penghulus about Online Marriage Law in Banjarmasin - Siti Muna Hayati; Husnul Khitam; Zainul Erfan; Afifah Amini (Journal of Islamic Law)
This article explores the perspectives of penghulus (marriage functionaries) in Banjarmasin regarding online marriage contracts, navigating the interplay between religious tradition and technological. Drawing upon differences in interpretation among Islamic jurists, the article elucidates varying views on the validation of marriage contracts, focusing on the concept of ittiḥād al-majlis (unity of session). This concept significantly shapes penghulus’ opinions on the legitimacy of online marriage contracts. Against this backdrop, the article analyses the factors driving discourse among penghulus regarding online marriage contracts and their implications within Banjarese community. Conducting interviews with 12 penghulus in Banjarmasin over a three-month period from September to November 2023, the study underscores the importance of religious tradition in Banjarmasin society and its adaptation to technological progress in interpreting Islamic law. The study finds that while the majority of penghulus oppose online marriage contracts, a minority endorse them under specific conditions. Those against them argue that ittiḥād al-majlis necessitates the physical presence of all parties in one location during the marriage contract process, whereas proponents contend that the virtual realm fulfills this criterion. These findings reflect the ongoing societal dialogue regarding the interpretation of religious doctrines and technological innovations, offering valuable insights into the intersection of religious tradition and technology in contemporary Islamic jurisprudence.